Repurposing Approved Drugs for Guiding COVID-19 Prophylaxis: A Systematic Review - Bruno Silva Andrade; Fernanda de Souza Rangel; Fernanda de Souza Rangel; Naiane Oliveira Santos; Andria dos Santos Freitas; Andria dos Santos Freitas; Wagner Rodrigues de Assis Soares; Wagner Rodrigues de Assis Soares; Sérgio Siqueira; Debmalya Barh; Aristóteles Góes-Neto; Alexander Birbrair; et al. (Frontiers Media S.A., 2020)
The SARS-CoV-2 outbreak originally appeared in China in December 2019 and became a global pandemic in March 2020. This infectious disease has directly affected public health and the world economy. Several palliative therapeutic treatments and prophylaxis strategies have been used to control the progress of this viral infection, including pre-(PrEP) and post-exposure prophylaxis. On the other hand, research groups around the world are still studying novel drug prophylaxis and treatment using repurposing approaches, as well as vaccination options, which are in different pre-clinical and clinical testing phases. This systematic review evaluated 1,228 articles from the PubMed and Scopus indexing databases, following the Kitchenham bibliographic searching protocol, with the aim to list drug candidates, potentially approved to be used as new options for SARS-CoV-2 prophylaxis clinical trials and medical protocols. In searching protocol, we used the following keywords: "Covid-19 or SARS-CoV-2" or "Coronavirus or 2019 nCoV," "prophylaxis," "prophylactic," "pre-exposure," "COVID-19 or SARS-CoV-2 Chemoprophylaxis," "repurposed," "strategies," "clinical," "trials," "anti-SARS-CoV-2," "anti-covid-19," "Antiviral," "Therapy prevention in vitro," in cells "and" human testing. After all protocol steps, we selected 60 articles that included: 15 studies with clinical data, 22 studies that used in vitro experiments, seven studies using animal models, and 18 studies performed with in silico experiments. Additionally, we included more 22 compounds between FDA approved drugs and drug-like like molecules, which were tested in large-scale screenings, as well as those repurposed approved drugs with new mechanism of actions. The drugs selected in this review can assist clinical studies and medical guidelines on the rational repurposing of known antiviral drugs for COVID-19 prophylaxis.